A New Philosophy of Society: Assemblages Theory and Social Complexity - DeLanda, Manuel (London New York, NY Bloomsbury Academic, 2013)
Manuel DeLanda is a distinguished writer, artist and philosopher. In his new book, he offers a fascinating look at how the contemporary world is characterized by an extraordinary social complexity. Since most social entities, from small communities to large nation-states, would disappear altogether if human minds ceased to exist, Delanda proposes a novel approach to social ontology that asserts the autonomy of social entities from the conceptions we have of them.
Keywords: 21st Century (2001-2100); Philosophy; Social science; Assemblage; Complexity